Wisdom in The Poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2017)
Ahmad Shawqi lived between 1868 and 1932 and witnessed many events experienced by Arab and Islamic nations. These events greatly impacted his life and his poetry. He lived in Egypt from before the occupation of semi-independence and lived through the Orabi Revolution. He witnessed the British occupation of Egypt as well as the national movement led by Mustafa Kamel and Mohamed Farid. He was later exiled to Spain by the British after the First World War in 1914 and the deposition of Khedive Abbas. He advocated the 1919 revolution that erupted in Egypt, praising the fighters and watching the national strife in exile. Upon victory, he returned from his exile in 1920. Shawqi was influenced by European lifestyle during his stay in France and Britain, but this did not take away his eastern origins and roots. Shawqi’s poetry immortalized the events of his time. His poetry collection reflects an important era in the history of Egypt, the State of the Caliphate, and all Arab countries.